Size Distribution and Growth Pattern of Kapiat (Barbonymus schwanefeldii) in Muaro Pijoan River, Jambi as a Scientific Basis for Development of Freshwater Aquaculture - Febrina Rolin; Lauura Hermala Yunita; Yoppie Wulanda; Yusyam Leni; Rizky Janatul Magwa (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
apiat (Barbonymus schwanefeldii) is one of the economically important freshwater fish found in the Muaro Pijoan River, Jambi. Intensive fishing pressure and water quality degradation due to anthropogenic activities pose threats to the sustainability of this fish population. This study aims to examine the size distribution and growth patterns of kapiat in the Muaro Pijoan River as a scientific basis for development of freshwater aquaculture. Sampling was conducted in October 2025 using traps and gillnets. A total of 83 kapiat were collected, consisting of 51 males and 32 females. Male fish had a total length range of 110–160 mm with a weight range of 20–55 g, while female fish had a total length range of 120–166 mm with a weight range of 21–71 g. The size distribution of male fish was dominated by the 134–141 mm size class (25 individuals), while female fish were dominated by the 156–164 mm size class (13 individuals). Length-weight relationship analysis showed that male fish exhibited a negative allometric growth pattern (b = 2.6399; R² = 0.7313), indicating that length growth was faster than weight gain. In contrast, female fish exhibited a positive allometric growth pattern (b = 3.4445; R² = 0.8998), indicating that weight gain was faster than length growth due to the gonadal maturation process. The relatively smaller size distribution compared to other populations suggests environmental influence on growth performance. These results provide baseline information for domestication strategies, broodstock selection, and feeding management in freshwater aquaculture systems